Efficient Gap‐Free Broadband Terahertz Generators Based on New Organic Quinolinium Single Crystals. Issue 21 (8th August 2019) - Shin, Myeong‐Hoon; Kim, Won Tae; Kim, Se‐In; Lee, Seung‐Heon; Yu, In Cheol; Jazbinsek, Mojca; Yoon, Woojin; Yun, Hoseop; Kim, Dongwook; Rotermund, Fabian; Kwon, O‐Pil
Abstract: New organic electro‐optic crystals containing orthogonally oriented electron‐withdrawing groups are developed for efficient and gap‐free THz wave generation with a very flat broadband spectral shape. These crystals consist of 2‐(4‐hydroxystyryl)‐1‐methylquinolinium (OHQ) cationic chromophores and nonplanar 4‐(trifluoromethoxy)benzenesulfonate (TFO) anions with orthogonally oriented highly electronegative trifluoromethoxy groups capable of strong hydrogen bonds. OHQ‐TFO crystals exhibit enhanced macroscopic optical nonlinearity with a second harmonic generation efficiency 2.3 times greater than that of benchmark OHQ‐based crystals with conventional planar anions. This enhancement is attributed to reduced edge‐to‐face π–π interactions between cations and anions due to the orthogonal orientation and electron‐withdrawing characteristics of trifluoromethoxy groups. Moreover, OHQ‐TFO crystals exhibit excellent THz wave characteristics generated by optical rectification; 0.52 mm thick OHQ‐TFO crystal generate a peak‐to‐peak THz electric field 15 times higher than that of inorganic standard 1.0 mm thick ZnTe crystal and a broader spectrum with an upper cut‐off frequency near 8 THz at pump wavelengths of 1140–1500 nm. Unlike previously reported state‐of‐the‐art organic electro‐optic salt crystals with strong phonon absorption in the frequency range of 0.8–3 THz, OHQ‐TFO crystals facilitate gap‐free broadband THz wave generation without strong absorption modulations due to the strong hydrogen bond ability of trifluoromethoxy groups. Abstract : Organic THz wave generators based on nonplanar anionic matchmakers with strongly electronegative and orthogonally oriented trifluoromethoxy groups capable of strong hydrogen bonds exhibit enhanced macroscopic second‐order nonlinear optical response when compared to conventional planar anions and show efficient gap‐free broadband THz wave generation with a very flat spectral shape.